Lagenandra wayambae (Araceae), a new endemic species from a freshwater swamp forest of Sri Lanka - Madola, Indrakheela; Yakandawala, Kapila; Yakandawala, Deepthi; Karunaratne, Senani (Phytotaxa, 2021)
A new species of Lagenandra (Araceae), is described and illustrated from Walauwewaththa Wathurana freshwater swamp forest, Bulathsinghala, Sri Lanka. Here we describe the new species as Lagenandra wayambae Madola, K. Yakandawala, D. Yakandawala and Karunaratne and provide a detailed description, drawing and colour photographs. We compare the morphology of L. wayambae with that of similar members of Lagenandra and conduct an assessment of its conservation status. A taxonomic key to the Sri Lankan Lagenandra is presented for easy identification. Recognizing a new endemic member enhances the number of Sri Lankan species to nine. According to the IUCN red data category guidelines L. wayambae qualifies for Critically Endangered category under Criterion B1ab (ii,iii,v) + B2ab (ii,iii,v).